Fostering inclusive co-creation in digital health - Alessandro Blasimme; Constantin Landers; Effy Vayena (npj Digital Medicine)
Research on responsible digital health innovation has typically focused on technical aspects such as the reliability and trustworthiness. More recently, work in responsible digital health innovation has started to recognize that, to address those concerns, stakeholder involvement is key. Aligning technological advancements with stakeholders’ needs requires deliberate and inclusive processes. Such processes must incorporate diverse perspectives, including those of the users of digital health technologies, such as healthcare practitionerss and patients.